Interactions of CO2 with formation waters, oil and minerals and CO2 storage at the Weyburn IEA EOR site, Saskatchewan, Canada. (October 2016) - Hutcheon, Ian; Shevalier, Maurice; Durocher, Kyle; Bloch, John; Johnson, Gareth; Nightingale, Michael; Mayer, Bernhard
Highlights: Oil is a significant reservoir for CO2 storage. Oil, saline water and supercritical CO2 are the largest co2 sinks. Over 50 years mineral storage is minimal but CO2 is redistributed into minerals, potentially dawsonite, over 1000's of years. Abstract: The Weyburn oil field in Saskatchewan, Canada, is hosted in Mississippian carbonates and has been subject to injection of CO2 since 2000. A detailed mineralogy study was completed as the basis for modeling of mineral storage of injected CO2 . Combining the mineralogy with kinetic reaction path models and water chemistry allows estimates of mineral storage of CO2 over 50 years of injection. These results, combined with estimates of pore volume, solubility of CO2 in oil and saline formation waters, and the initial and final pore volume saturation with respect to oil, saline water and gas/supercritical fluid allow an estimate of CO2 stored in saline water, oil and minerals over 50 years of CO2 injection. Most injected CO2 is stored in oil (6.5 × 10 6 –1.3 × 10 7 t), followed closely by storage in supercritical CO2 (7.2 × 10 6 t) with saline formation water (1.5–2 × 10 6 t) and mineral storage (2–6 × 10 5 t) being the smallest sinks. If the mineral dawsonite forms, as modeling suggests, the majority of CO2 dissolved in oil and saline formation water will be redistributed into minerals over a period of approximately 5000 years. The composition of produced fluids from a baseline sampling program, when compared to produced fluids taken three years after injection commenced, suggest that dawsonite is increasingly stable as pH decreases due to CO2 injection. The results suggest that hydrocarbon reservoirs that contain low gravity oil and little or no initial gas saturation prior to CO2 injection, may store the majority of injected CO2 solubilized in oil, making such reservoirs the preferred targets for combined enhanced oil recovery-CO2 storage projects.